(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
Chromosomal diseases form a large group of genetic diseases. They make up the bulk of all reproductive losses, congenital malformations, and are the causes of mental and physical development in children. This article presents the results of cytogenetic studies in early pregnancy. According to statistical data, the conclusions of the research work are made.